Dissecting the role of MADS-box genes in monocot floral development and diversity - Callens, Cindy; Tucker, Matthew R.; Zhang, Dabing; Wilson, Zoe (Oxford University Press, 2018)
Many monocot plants have high social and economic value. These include grasses such as rice (Oryza sativa), wheat (Triticum aestivum) and barley (Hordeum vulgare), which produce soft commodities for many food and beverage industries, and ornamental flowers like lily (Lilium longiflorum) and orchid (Oncidium Gower Ramsey), which represent an important component of international flower markets. There is constant pressure to improve the development and diversity of these species with a significant emphasis on flower development, and this is particularly relevant considering the impact of changing environments on reproduction and thus yield. MADS-box proteins are a family of transcription factors that contain a conserved 56 amino acid MADS-box motif. In plants, attention has been devoted to characterisation of this family due to their roles in inflorescence and flower development, which holds promise for the modification of floral architecture for plant breeding. This has been explored in diverse angiosperms, but particularly the dicot model Arabidopsis thaliana. The focus of this review is on the less-well characterised roles of the MADS-box proteins in monocot flower development and how changes in MADS-box proteins throughout evolution may have contributed to creating a diverse range of flowers. Examining these changes within the monocots can identify the importance of certain genes and pinpoint those which might be useful in future crop improvement and breeding strategies.